ANALISIS KESANTUNAN BERBAHASA PADA NOVEL “ME AND MY HEART” KARYA EVA RIYANTI LUBIS - Asep Solihin; Junita Junita; Sary Sukawati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the fact that the principle of politeness is important both in oral and written. Novels as writing must also use levels and conversations that include the principle of politeness in language. The problems in this study are; "How is the use of language politeness in a novel called Me And My Heart by Eva RiyantyLubis. The purpose of this study is to describe the use of language politeness in a novel entitled Me And My Heart by Eva RiyantyLubis. In this research activity, the method used is a descriptive method. The data in this study are dialogues that contain the maxims of politeness in language. While the data sources in this study are conversations, data collection techniques in this study use reading, note-taking, literature, analysis techniques. Based on the results of the study it was concluded that in the novel entitled Me And My Heart by Eva RiyantyLubis it did not fulfill the six maxims of politeness in the language according to Leech, which collected 52 utterances using the principle of politeness in language including a) Maxim's conclusions. b) Maxim agreement. c) Maxim wisdom. d) Maxim of generosity. e) Maxim simplicity. f) Maximally reward.